System of differential equations with a strong turning point - Bobochko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The uniform asymptotics of a solution of a system of singularly perturbed differential equations with strong turning point is constructed. We study the case where the boundary operator is analytic with respect to a small parameter.